Walter De Maria Conceptual Art, Minimal Art, Land Art - Kellein, Thomas 1955- (Schirmer/Mosel, 2023)
A monographic survey of Walter De Maria's oeuvre of Minimal Art, Concept Art, and Land Art, from his almost invisible early drawings to wood and steel sculptures, gallery installations such as the 1968 Munich Earth Room, and Land Art icons like Lightning Field in New Mexico
Notes: This essay is based on part of my dissertation, titled "Das Großprojekt als 'Projektion'. Neue künstlerische Maßstäbe um 1960 in Paris, im Rheinland und in New York," which I submitted to Department 09 of the Universität Hamburg in 1982. In 1987, I revised this text for the Staatsgalerie Stuttgart's exhibition catalogue "Walter De Maria. 5 Kontinente Skulptur", adding two new chapters for that publication. (Seite 136)
63 color illustrations
Keywords: De Maria, Walter -- 1935-2013; Kunst; Walter De Maria; Minimal Art